PREGNANCY RATE OF RECIPIENT COWS AFTER TRANSFER OF IN VITRO-PRODUCED NELLORE EMBRYOS - Jaguszeski, Mônica Zucheli (2019)
The objective of this study was to evaluate the pregnancy rate (PR) of cows of six farms in Bolivia and in the states of Acre and Rondônia in Brazil after the transfer of 4,321 in vitro Nellore embryos produced by a private company, in 2015 to 2016. The effects of the farm location, year of embryo transfer (ET), season of ET, number of previous ET per recipient, and embryo development stage on the PR of the recipient cow (chi square p<0.05) were evaluated. The PR of the six evaluated farms were similar, with an average of 45.15%. The farm location, year of ET (2015 or 2016), and season of ET (rainy or dry season) did not affect the PR (p>0.05). The PR found after embryo transfer for recipient cows that had already been used once (45.58%) or twice (43.40%) for this purpose were higher than that of recipient cows used three to eight times (29.01%) (p<0.05). ET at expanded or hatched blastocyst stage resulted in higher PR (47.35%) when compared to the ET at morula or initial blastocyst (41.06%) and at blastocyst stage (43%) (p<0.05), which did not differ from each other (p>0.05). Under the conditions of this study, the transfer of in vitro-produced Nellore embryos at advanced development stages (expanded or hatched blastocyst) results in higher PR in cows that had been used once or twice for this purpose.